PENGARUH KUALITAS PELAYANAN, FASILITAS, HARGA DAN LOKASI TERHADAP KEPUTUSAN KONSUMEN UNTUK MENGINAP DI HOTEL SAKURA PALANGKA RAYA - Sri Hartini (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2017)
Hospitality service companies must have an ability to design marketing strategy so that it can provide influences on the customers to stay, one of which is by knowing any factors giving influences on the customer decision. The factors giving influences on the customer decision to stay are service quality, facility, price and location. This research aims to know the influences of service quality, facility, price and location on the customer decision and which variable has the most influences of the service quality, facility, price and location on the customer decision. This research population is Sakura Palangka Raya Hotel customers.The samples were 115 consumers taken by incidental sampling technique. The variables in this research are service quality, facility, price and location as the independent variables and decision to stay as the dependent variable. The data collection methods were by questionnaire and documentation. The instruments were tested the validity and reliability. Data analysis used was percentage descriptive analysis and multiple regression analysis. The partial test result was obtained tcountof service quality by 2,086 with probability by 0,039<0,05, meaning that there is significant effect of service quality on the decision to stay and its contribution by 3,80%,tcountof facility by 2,532 with probability by 0,013<0,05meaning that there is significant effect of facility on the decision to stay and its contribution by 5,25%,tcountof price by 2,254with probability by 0,026<0,05 meaning that there is significant effect of price on the decision to stay and its contribution by 4,41%, tcountof location by 3,284 with probability by 0,001<0,05 meaning that there is significant effect of location on the decision to stay and its contribution by 8,94%.The regression modelis Ŷ=-2,809+ 0,283X1+0,263X2+0,177X3 +0,349X4.The stimulant test result was obtained Fcountby 45,435with probability by 0,000<0,05, meaning that there is significant effect of service quality, facility, price, and location on the decision to stay in Sekura Palangka Raya Hotel and the effect contribution by 60,9%.Keywords: Service Quality, Facility, Location and Decision to Stay